EFEKTIFITAS MODEL PROJECT BASED LEARNING BERBANTUAN VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR IPAS MATERI ORGAN PERNAPASAN MANUSIA DAN FUNGSINYA KELAS 5 SEKOLAH DASAR NEGERI WATUPECAH REMBANG - Sholikhatun Nikmah; Ifa Seftia Rakhma Widiyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effectiveness of the Project Based Learning model on science learning outcomes (IPAS) regarding the topic of human respiratory organs and their functions among fifth-grade students at SDN Watupecah, Rembang Regency. This research is a quantitative study using a one- group pretest-posttest design. The population in this study consisted of all fifth- grade students at SDN Watupecah in the 2024/2025 academic year, with a sample of 20 students selected using non-probability sampling with a simple random sampling technique. Data collection was carried out through interviews, observation, tests, and documentation. The results of the normality test indicated that the pretest and posttest data were normally distributed. The t-test results showed that the average pretest score was 56.55 and the average posttest score was 80.4, with N = 20. The calculated t-value was 4.024, while the critical t-value at a significance level of 0.05 with 19 degrees of freedom was 2.093. Since the calculated t-value is greater than the critical t-value (t_calculated > t_table), the null hypothesis (H₀) is rejected and the alternative hypothesis (H₁) is accepted. Therefore, it can be concluded that the Project Based Learning model is effective in improving science learning outcomes on the topic of human respiratory organs and their functions among fifth-grade students at SDN Watupecah, Rembang Regency. Based on the results, the researcher suggests that the Project Based Learning model can be used as a variation in teaching, as its implementation